Some Special Sequences in Fuzzy Graphs. Issue 1 (1st March 2016) - Mathew, Jill K.; Mathew, Sunil
Abstract: In a fuzzy graph, the edges are mainly classified into α, β and δ . In this paper, some sequences in fuzzy graphs are introduced, whose concepts are based on the classification of edges. Besides, characterizations for blocks in fuzzy graphs and fuzzy trees are obtained. It is shown that β sequence of a fuzzy tree is a zero sequence and α sequence of a block is a binary sequence.